Efficacy of fungicides in controlling late blight of potato - Anwar, MM; Parveen, A; Hossain, MM; Mahamud, NU; Roy, RK (Progressive Agriculture, 2015)
Potato cultivars grown in Bangladesh have low levels of general resistance to late blight. As such, most commercial potato farmers rely on fungicide applications for control of Phytophthora infestans, the causal agent of late blight. Management of late blight of potato requires an integrated approach that includes rotation with non-hosts, resistant cultivars, cultural practices, and fungicides. The study on efficacy of some new fungicides against late blight disease of potato was conducted at ARS, Alamnagar Rangpur during rabi season 2010-2011 to select suitable fungicides against late blight of potato. Thirteen different fungicides were tested and all the tested fungicides showed significantly better performance over control. Considering percentage disease incidence T4,T6 and T12 showed better performance than all other treatment. In case of T4,T6 and T12 treatment disease reduction was more than 80 % over control. Significantly the highest tuber yield 25.5 t ha-1was obtained from T3 which was statistically similar to the yield of T2,T5 , T6, T9, T10, T11and T12 treatment whereas the lowest tuber yield 14.5 t ha-1 was obtained from control treatment. Field experiment was conducted from 2010 to 2011 to investigate the comparative efficacy of the fungicides. In the field, applications of fungicide that preceded the largest incremental increase in disease incidence provided the best control of disease or increased yield. Progressive Agriculture 26 (2): 103-108, 2015